Monetary policy and macro economic indicators: A review of a developing country's perspectives 2002-2017 - Simon Akumbo Eugene Mbilla; Peter Akurigo Atindaana; Samuel Gameli Gadzo; Abiola Adeniyi; Idrisu Salifu (Cogent Economics & Finance, 2021)
The purpose of the study was to examine the effect of monetary policy on key macroeconomic indicators in Ghana. The study used annual time series data from 2002 to 2017, which was sourced from the World Development Indicator (WDI) and the Bank of Ghana (BOG). The data were converted to Quarterly data between 2002Q1 and 2017Q4, which covers a sample period of sixteen years. The study employed the Autoregressive Distributed Lagged Model (ARDL) for analyzing the data. Unit root test was conducted using the Augmented Dickey-Fuller (ADF) tests, and the results of the analysis exhibited a cointegration realtionship among the variables of order one (1). Monetary policy changes affected lending rates by (0.32%) compared to the other variables. Overall, the results suggests that monetary policy affects macro economic indicators performance in Ghana. Based on the foregoing, the paper recommends that, in efforts to enhance the effectiveness of monetary policy, the need for policy intervention in determining the stance of fiscal policies, develop financial markets, and liberalize controlled interest rates.
Keywords: 330; Average lending rates; inflation rates; lending rates; monetary policy rate